2009
DOI: 10.1080/07420520902758311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Light on the Reproductive System of European Sea Bass Gauged by Alterations of Circadian Variations during Their First Reproductive Cycle

Abstract: The European sea bass is a short-day breeder, a characteristic that is highly valued in aquaculture. A 2 high percentage of males of this species mature precociously before reaching commercial size,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…This timing would be, therefore, critical for the control of the reproductive cycle in this species. Consequently, photoperiod manipulation in sea bass affected both plasma melatonin and receptor mRNA oscillations, and significantly altered the circadian and annual profile of several reproductive hormones, preventing the achievement of the reproductive process [35,37,42,51]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This timing would be, therefore, critical for the control of the reproductive cycle in this species. Consequently, photoperiod manipulation in sea bass affected both plasma melatonin and receptor mRNA oscillations, and significantly altered the circadian and annual profile of several reproductive hormones, preventing the achievement of the reproductive process [35,37,42,51]. …”
Section: Discussionmentioning
confidence: 99%
“…Some reproductive hormones, including GnRH, exhibit daily [37] and/or seasonal variations [38–41]. In addition, changes in photoperiod conditions can influence reproductive performance and puberty in sea bass by altering circadian and seasonal variations of reproductive hormones, as well as melatonin content and/or melatonin binding sites [34,35,42]. …”
Section: Introductionmentioning
confidence: 99%
“…In European sea bass, males can attain precocious puberty during their first reproductive cycle . Different studies (Begtashi et al, 2004;Felip et al, 2008;Bayarri et al, 2009;Rodríguez et al, 2012b) have shown that fish which mature precociously are larger than non-precocious specimens, and in fact a significant positive correlation was observed between the spermiation rate and the weight and length of one-year-old male European sea bass (Rodríguez et al, 2012b). The basis for this observation is the high energy demands of the first gonadal maturation, which only occurs in fish that have attained a certain size, as they have enough reserves to engage in this process with any certainty of success (Rowe et al, 1991).…”
Section: Sex Differentiation Anticipated Puberty (Precocity) and Pubmentioning
confidence: 93%
“…Such a marker would allow the determination of the precocity rate, the early separation of precocious males, and facility the prevention of early puberty in a given population. Different studies performed in male European sea bass have so far stressed that size is still the most reliable early marker for non-lethal prediction of precocious puberty (Begtashi et al, 2004;Felip et al, 2008;Carrillo et al, 2009;Bayarri et al, 2009;Rodríguez et al, 2012b). A deeper analysis combining several markers or analyzing new ones should be performed to refine this prediction.…”
Section: Importance Of the Photosensitive Periodmentioning
confidence: 96%
“…The result improved considerably, though still missing almost one half of the pertinent papers, when the same heading was used as a text entry to search not only the MeSH headings but also the abstracts and titles of the references: 119 (54.3%) of the chronobiologic articles were identified. ''Chronobiology disorders'' retrieved only three (15.8%) (Kantermann and Roenneberg 2009;Reinberg et al 2010;Selvi et al 2010) and missed 16 articles dealing with disruptions of cycles of bodily functions or activities Bayarri et al 2009;Canal et al 2009;Cayetanot et al 2009;Edwards and Waterhouse 2009;Farhat et al 2009;Minana-Solis et al 2009;Smith VM et al 2009;Terrien et al 2009;van der Leest et al 2009;Vera et al 2009;Vivanco et al 2009;Ishibashi et al 2010;Valdez et al 2010;Yamamura et al 2010;Zubidat et al 2010).…”
Section: Resultsmentioning
confidence: 98%